Requirements of the Small and Medium Enterprises Sector in the State of Kuwait - Challenges and Prospects - Al-Mudhaf, Wedad Fahad; Al Mershed, Afaf Mershed (Journal of Economic, Administrative and Legal Sciences, 2021)
Small and medium companies represent great importance in creating new job opportunities, and the current and potential high growth rates of these projects have proven their superior ability to influence the future of any country. However, there remain many barriers that impede the development and growth of these projects and limit their development, for example; difficulties in financing, difficulties in marketing, lack of specialized workers, etc. Therefore, this research focuses on the most important difficulties and challenges facing small and medium enterprises in Kuwait, and the factors that help their success and continuity, as we presented through this study some success factors through laws legislation, or financial support, in addition to mentioning the most important factors that help the success of small and medium enterprises in Kuwait. At the end of the research, a set of recommendations and proposals were mentioned that contribute significantly to the viability of small and medium-sized companies
Keywords: small and medium enterprises; financing; private sector; efficiency